Feedback Linearization Control of a Dual Active Bridge Converter Feeding a Constant Power Load - Rodríguez, Federico (2022)
This paper presents a control based on feedback linearization technique to control a Dual Active Bridge (DAB) Converter feeding a constant power load (CPL). The proposed control law requires knowledge of the load power and its time derivative, for which a non-linear reduced-order observer isdesigned to estimate these variables. Simulation results are presented to validate the proposed control, showing a good dynamic response of the system under significant variations in the transferred power and changes in the direction of the energy flow.